Some remarks on hydrogen-assisted electrical conductivity in olivine and other minerals - Shun-ichiro Karato (Progress in Earth and Planetary Science, 2019)
Abstract Electrical conductivity in minerals is sensitive to hydrogen content, and therefore, it is a potentially important property from which one can infer hydrogen (water) distribution in the mantle. However, there has been much confusion in the reported results on hydrogen-assisted conductivity. In this paper, I review the existing experimental observations on hydrogen-enhanced electrical conductivity in olivine and other minerals to identify the causes of confusion. Hydrogen loss as well as hydrogen gain could occur during a conductivity measurement at high pressures and temperatures. Particularly important is the unrecognized hydrogen gain during an experiment that could lead to a large degree of error. Many experiments were conducted under the conditions where specimens were super-saturated with hydrogen making the validity of those results unclear. A model for hydrogen loss is developed showing a strategy by which hydrogen loss can be minimized. When one selects the experimental results in which the influence of hydrogen loss/gain are carefully examined, there is no major discrepancy among the results from different laboratories except differences between the results from low and high temperatures. Differences between low-temperature and high-temperature results are caused by the change in conduction mechanism. At low temperatures, conduction is due to the migration of interstitial (“free”) proton and is nearly isotropic, whereas conduction at high temperatures is due to the migration of two protons at M-site that is highly anisotropic. There is no evidence for substantial concentration dependence of activation enthalpy. Observed exceptionally large concentration dependence reported by Poe et al. (Phys Earth Planet Inter 181:103-111, 2010) is inconsistent with all other reports and is likely caused by some experimental artifact. Experimental results in the high-temperature regime explain a majority of geophysical observations on the conductivity of the oceanic asthenosphere: partial melting is not needed in most regions and is rather inconsistent with the observations on the matured oceanic mantle. Exception is the asthenosphere near the ridge and/or near the trench where very high conductivity (~ 0.1 S/m) is reported at the top of the asthenosphere. Partial melting might play some role in these regions. Electrical conductivity in the continental lithosphere cannot be attributed entirely to olivine. An important role of orthopyroxene and/or other minor materials (graphite, sulfide) is needed to explain high conductivity reported in some regions such as Bushveld in South Africa. The largest remaining uncertainty is the degree to which hydrogen affects electrical conductivity in the lower mantle minerals. Determining the influence of hydrogen on electrical conductivity in lower mantle minerals is critical to make progress in understanding the global water circulation.